THE INFLUENCE OF ISLAMIC CORPORATE SOCIAL RESPONSIBILITY AND ISLAMICITY PERFORMANCE INDEX DISCLOSURE ON COMPANY REPUTATION: AN EMPIRICAL STUDY OF SHARIA BANK IN INDONESIA - Muhammad Mumtaza Walad; Tuti Anggraini; Nur Santri Yanti (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This research aims to influence macroeconomic variables on economic growth in Indonesia. Economic growth is seen as a development of economic activity which causes goods and services produced in a country to increase. This research method is quantitative research with secondary data in the 2012-2021 observation period. Secondary data collection uses the documentation method for data on reports of total exchange rates, inflation, interest rates and economic growth from BPS, BPPRP and BPKAP, the data collected is analyzed using multiple linear regression using the eviews 9 computer program. Research results show 1) Value Exchange rate from the results of the multiple linear regression test has a negative and significant effect on economic growth during the 2012-2021 period, meaning that every increase in the exchange rate will reduce economic growth by -1.28%. 2) Inflation has a positive and significant effect on economic growth in 2012-2021, increasing economic growth by 3.83%. 3) The BI-7 Day Reverse Repo Rate (BI7DRR) has no significant effect on economic growth in 2012-2021 and has no impact whatsoever on economic growth. This research aims to determine the influence of Islamic Corporate Social Responsibility on the reputation of Sharia banking companies in Indonesia and the Islamicity Performance Index on the reputation of Sharia banking companies in Indonesia for the 2019-2022 period. This research is a quantitative study and the data used in this research is secondary data. starting from annual statements and statements about the sustainability of Sharia banks. The sample collection technique uses a purposive sampling method, meaning the sample selection method uses the specified collection method, obtained from 3 Sharia commercial banks which were used as research samples during 2019-2022. Data analysis uses simple Linear Regression Analysis. The research results show that ICSR and IPI disclosures have a positive and significant influence on corporate reputation at Sharia banks in Indonesia. This research contributes to know about the influence of Islamic Corporate Social Responsibility on the reputation of Sharia banking companies in Indonesia and the Islamicity Performance Index on the reputation of Sharia banking companies in Indonesia for the 2019-2022 period. Not only that, this research can be a reference for further research.